A fuzzy model for path delay fault detection. - Favalli, M.
A fuzzy model is proposed to analyze the effectiveness of test pairs targeting path delay faults. This model is accurate enough to rank nonrobust tests by accounting for conditions not considered in existing models. It remains fully consistent with the traditional test robustness analysis. Finally, it also provides a coverage metric to be used to rank whole test sets. The proposed model has been implemented in a logic level path delay fault simulator. Its accuracy has been validated, for a set of combinational benchmarks, by means of a Monte Carlo logic-level event-driven path delay fault simulator.
Keywords: Monte Carlo logic; Combinational benchmarks; Fault simulation; Fuzzy logic; Fuzzy model; Logic level path; Path delay fault detection; Robustness analysis